Konsep Teologi menurut Mukti Ali dan Millard J. Erickson - Dasopang, Isma Azizah (AHKAM, 2023)
The problem in the field of theology is that conflicts often occur regarding the understanding of divinity when one religious concept is compared to another. The purpose of this research according to religious studies is for the benefit of SAA, namely to find out Mukti Ali and Millard J. Erickson and to compare to find out the differences and similarities that occur between Mukti Ali and Millard J. Erickson so that conclusions can be drawn between the two views. in this research includes library research (library research), namely collecting data sourced from the library, either in the form of research reports, journals, books related to the title of this research. Data was collected by collecting various references with other publications that are still related to the object under study. The research findings illustrate that there are differences regarding the concept of theology when compared to the thoughts of Mukti Ali as an Islamic thinker, and Millard J. Ericson who is always a Christian thinker. The results of this study indicate that Theology according to Mukti Ali is a science which believes that Allah is One and there is nothing similar to Him. Meanwhile, according to Millard J. Erickson, theology is how we believe and understand God that God consists of God the Father, God the Son and God the Holy Spirit. Mukti Ali's view on theology is that theology must be studied because by studying theology we will understand more about divinity and we can know the characteristics of God. According to Millard J. Erickson, by understanding theology we can understand how the trinity is and we can know that God's love is so great that He sacrificed his only son to atone for human sins.